Demographic and clinical analysis of pediatric poisoning in intensive care (Annals of Medical Research, 2024)
Aim: This study aims to improve the understanding of childhood poisoning by examining the demographic, clinical, and laboratory characteristics of critically ill patients admitted to the pediatric intensive care unit (PICU).Materials and Methods: This retrospective study analyzed 209 pediatric poisoning cases admitted to the PICU, accounting for 4.2% of total admissions. Data on age, gender, exposure route, location, time to admission, symptoms, examination findings, treatments, and PICU stay duration were collected. Patients were categorized as survivors or non-survivors, and statistical analyses were conducted to identify predictors of mortality.Results: Of the 209 cases, 62.2% were female, with a mean age of 8.75 years. Accidental poisoning was more common in children under five (56.5%), while suicide attempts (36.8%) and substance abuse (6.7%) were prevalent among adolescents. Girls had higher rates of accidental and suicidal poisoning, while boys were more involved in substance abuse. The majority of exposures were oral (90.9%) and occurred indoors (86.1%). Drug-related poisonings accounted for 53.6% of cases, with central nervous system drugs (12.4%) being the most common agents, followed by corrosive substances (7.9%). Mechanical ventilation was required in 25.4% of accidental, 9% of suicidal, and 14% of substance abuse cases. The overall mortality rate was 8.2%, with prolonged PICU stay and the absence of activated charcoal identified as significant predictors of mortality.Conclusion: This study underscores the critical need for age- and gender-specific preventive measures to mitigate pediatric poisoning. Safe storage of hazardous substances and prompt medical intervention, such as timely administration of activated charcoal, are critical to reducing mortality. Prolonged PICU stays have been associated with increased mortality, often indicating more severe cases. Unintentional poisonings in younger children, largely due to inadequate supervision, highlight the importance of preventive strategies, while intentional poisonings in adolescents require closer monitoring and mental health interventions.
Keywords: Activated charcoal; Drug abuse; Pediatrics; Poisoning; Suicide attempt; Substance abuse